Karakteristik Mutu Produk Susu Kedelai Tanpa Merek yang Beredar di Kota Mataram - Komalasari, Husnita; Manurung, Nancy Eka Putri; Yoga, Wahyu Krisna (Food Scientia : Journal of Food Science and Technology, 2024)
Soy milk is a food product made from processed soybeans which has a high source of nutrition and as a source of vegetable protein. The aim of this study is to determine the quality characteristics of unbranded soy milk products marketed in Mataram City and the influence of storage methods and time. The method used was a descriptive and experimental method with a completely randomized design (3 treatments and 3 replications). Data were analyzed using ANOVA a=5% with Tukey and Dunnet further tests. The test results showed that the quality characteristics of unbranded soy milk marketed in Mataram city have several parameters that are and are’nt in accordance with SNI. Parameters that comply with SNI are pH (6.9), normal color and aroma. Meanwhile, what does not comply with SNI is the number of microbes. In addition, several parameters do not yet have standards such as viscosity (1.18 cP), color L* (74.45), a* (-6.14), b* (7.46), °hue (-50.56 ), TPT (15.5), appearance (homogeneous) and texture (liquid). Storage time and method have a significant differences on the physicochemical properties of the product except for the color parameter b*. It is known that storage at room temperature for 48 hours (SK2) results in soy milk not comply with SNI standards, and cold storage (SK2D) is able to maintain the quality of soy milk better than at room temperature. The best quality and treatment characteristics are SK0, but microbial contamination still exceeds the SNI threshold.